Przestępstwo fałszowania świadectwa depozytowego - Jurzak, Kamil; Tyralik, Mikołaj (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The paper discusses the amendment to the Act on Trading in Financial Instruments which introduced Article 178i criminalizing forgery of a certificate of deposit, or use of such forged document. Taking into account the current provisions of the Polish Criminal Code concerning false documents, the authors conclude that the amendment, in the commented scope, is unnecessary. Moreover, no relevant amendments have been made to the Polish Code of Commercial Companies, therefore Article 18 of this act will not apply to the persons convicted under Article 178i of the Act on Trading in Financial Instruments.